Activation of Endothelial Nitric Oxide Synthase by Proanthocyanidin-Rich Fraction From Croton celtidifolius (Euphorbiaceae): Involvement of Extracellular Calcium Influx in Rat Thoracic Aorta - Silvia DalBó; Suelen Goulart; Heros Horst; Moacir Geraldo Pizzolatti; Rosa Maria Ribeiro- (Elsevier, 2008)
The present study investigates the mechanisms related to the endogenous nitric oxide synthase (eNOS) activation in the relaxant effects of a proanthocyanidin-rich fraction (PRF), obtained from Croton celtidifolius BAILL barks, in rat thoracic aorta rings with endothelium. In vessels pre-contracted with phenylephrine (Phe), PRF (0.1 - 100 μg/mL) induced a concentration-dependent relaxation. This effect was significantly reduced by endothelium denudation, by Nω-nitro-L-arginine, and by 1H[1,2,3]oxadiazolo[4,3-alpha]quinoxalin. However, the vasorelaxant effect was not altered by indomethacin, atropine, tetraethylammonium, and charybdotoxin plus apamin. In thoracic aorta rings pre-contracted with phorbol-12,13-dibuyrate, PRF also induced a concentration-dependent relaxation. The PRF-induced relaxation disappeared in the absence of extracellular calcium in the medium and decreased significantly in the presence of lanthanum. A sulfhydryl alkylating agent, N-ethylmaleimide, and a phospholipase C (PLC) blocker, neomycin, significantly decreased PRF-induced vasorelaxation. In vessels pre-contracted with Phe, the PRF-induced vasorelaxant effect was not altered by quinacrine and ONO-RS-082, genistein and thyrphostin A-23, GF109203, and pertussis toxin and cholera toxin. The results suggest that the PRF-induced vasorelaxant effect is endothelium-dependent and involves the NO/cGMP pathway. We hypothesize that the activation of eNOS is due to an increase of intracellular calcium derived from PLC activation and an N-ethylmaleimide sensitive pathway. Keywords:: Croton celtidifolius, proanthocyanidin, vasorelaxation, nitric oxide, extracellular calcium